2007
DOI: 10.1103/physrevb.75.146501
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Essence of intrinsic tunneling: Distinguishing intrinsic features from artifacts”

Abstract: In a recent paper V.Zavaritsky has argued that interlayer (c− axis) current-voltage characteristics of high temperature superconductors (HTSC) are Ohmic, and has claimed to disprove all findings of intrinsic tunnelling spectroscopy, as well as existence of the interlayer tunnelling and the intrinsic Josephson effect in HTSC, as such.In this comment I demonstrate, that the genuine interlayer current-voltage characteristics are strongly non-Ohmic, which undermines the basic postulate and the logical construction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Since the ITS is sensitive to bias-induced self-heating, extreme care should be taken, as in this study, to keep the sample temperature constant within a tolerance limit over the whole bias sweeping range. However, as demonstrated by Krasnov et al, 16,43 most of the essential observations on a PG feature remain valid even in the earlier ITS results. Thus, ITS, with a precautious measure taken to eliminate self-heating, should provide a very useful experimental tool to investigate the electronic excitation spectrum of highly anisotropic materials containing naturally grown tunneling junctions.…”
Section: Discussionmentioning
confidence: 62%
“…Since the ITS is sensitive to bias-induced self-heating, extreme care should be taken, as in this study, to keep the sample temperature constant within a tolerance limit over the whole bias sweeping range. However, as demonstrated by Krasnov et al, 16,43 most of the essential observations on a PG feature remain valid even in the earlier ITS results. Thus, ITS, with a precautious measure taken to eliminate self-heating, should provide a very useful experimental tool to investigate the electronic excitation spectrum of highly anisotropic materials containing naturally grown tunneling junctions.…”
Section: Discussionmentioning
confidence: 62%
“…iii) Direct measurement of mesa temperatures for small ITS mesas showed that at the peak T m remains well below T c [9] [1] . Recently this conclusion was confirmed by "intrinsic" detection of T m [2,3]. In this case, T −dependent characteristics of the mesa itself were used for determination of T m , avoiding any possible lag between the mesa and the thermometer.…”
mentioning
confidence: 93%
“…Self-heating in ITS is actively discussed [2] for more than a decade (see Ref. [3] for a recent summary).…”
mentioning
confidence: 99%
“…The postulate that the self-heating is the only origin of the I-V non-linearities [35] does not stand up well to the following qualitative and simple reasoning (see also other arguments in Ref. [36]).…”
Section: Newton's Law Of Coolingmentioning
confidence: 93%